Impact of the Corona virus Pandemic on the Global Economy - Shokirov, M. M. (Universitas Muhammadiyah Sidoarjo, 2021)
The article discusses the main consequences of the COVID-19 pandemic for the economy. The authors emphasize that the outbreak of the virus has become one of the most serious threats to the global economy and financial markets. It is noted that concerns about the impact of the coronavirus on the global economy have stirred up markets around the world: stock prices and bond yields have fallen sharply. Forecasts of GDP decline in leading countries and regions are given; the main possible methods of mitigating the effects of the pandemic on the economies of developing countries are considered.